Color in dentistry a clinical guide to predictable esthetics - Chu, Stephen J.; Sailer, Irena; Paravina, Rade D.; Chu, Stephen J. ([S.l.] : Quintessence Publishing Co, Inc., 2019)
Predictable shade matching in dentistry remains a significant challenge for clinicians in daily practice. Color is an important aspect in the esthetics of teeth and dental restoration fabrication, and color discrepancy can mar restorative results, even when other aspects (marginal fit, occlusion, and morphology) are adequate. This book provides step-by-step protocols to help dental professionals accurately match, communicate, and reproduce the color of teeth and gingiva. These authors demonstrate how to implement color science in simple problem-solving instructions for predictable esthetics in both clinical protocols and laboratory techniques. An extensive presentation of clinical cases is included to illustrate the use of recommended protocols in general practice. An outstanding contribution to the practice and theory of color management in contemporary dentistry.
Color in dentistry : a clinical guide to predictable esthetics -- Contents -- Foreword -- Preface -- Chapter one -- Color Education and Training -- Chapter two -- Color Theory -- Chapter three -- Elements Affecting Color -- Chapter four -- The United Colors of Dentistry: White, Pink, and Skin -- Chapter five -- Conventional Visual Shade Matching -- Chapter six -- Technology-Based Shade Matching -- Chapter seven -- Digital Photography -- Chapter eight -- Material Selection -- Chapter nine -- Clinical Management of hard and soft tissue discolorations -- Chapter ten -- Esthetics with Pink Restorative Materials -- Chapter eleven -- Predictable Color Reproduction and Verification -- Chapter twelve -- Clinical Cases -- Appendix -- Index.
Includes bibliographical references and index.
Keywords: Dental Prosthesis Design; Esthetics, Dental; Prosthesis Coloring